The relationship between the factors of work-life balance and job satisfaction among support staff in Construction Industry Development Board (CIDB) Kuching , Sarawak/Hani Yusra Zul-Hisan - Zul-Hisan, Hani Yusra (2018)
This study is to the relationship between work life balance and job satisfaction that divided into three categories which is working hours, working conditions and work pressures that give huge impact towards their job satisfaction in the organizations. The sample consists of 100 peoples in CIDB Kuching Sarawak.This was accomplished through quantitative method of data collection namely questionnaire. This study uses non-probability that is convenience sampling to select the sample size that consists 100 staff in CIDB Kuching Sarawak. Pearson correlation and regression analysis was carried out for the collected data. For the data collection, the data has been collected using structured questionnaire that divided into three sections. Section A focused on the demographic background of the respondent, section B consists of the factors work life balance was focused on the organization.The data were analyses using descriptive statistical analysis (SPSS 23.00 which consists mean, standard deviation and correlation coefficient analysis. The correlation analysis revealed that normative commitment has a low and significant relationships towards job satisfaction. This finding indicated that it is recommends for future studies to further investigate the different types of work life balance and job. satisfaction among their employees towards their organizations.